Re-Reading David Adams Richards: Ironies of Allegory in Mercy among the Children - Robinson, Jack (Studies in Canadian Literature, 2011)
David Adams Richards’s literary reputation as a single-minded essentialist, or sometimes his personal reputation as the Miramichi scrapper, distracts critics from a diligent and responsible consideration of his texts. A reading of Mercy among the Children attentive to the novel’s complexities and indeterminacies shows it to be suffused or saturated with irony, as seen in the multi-levelled insights of its astringent humour. The upshot of these multiple ironies is that the tone becomes multi-faceted, character is destabilized, and traditional allegory’s assignation of one-to-one equivalencies is dislodged and becomes no longer adequate to describe the text at hand. Richards is practicing a kind of allegory that conducts an ongoing and finally unresolved debate about the narrative’s meanings while in the process of constructing them.